Khai phá dữ liệu trong thư viện số - Đậu, Mạnh Hoàn (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Based on the characteristics of data mining and digital library, the article discusses some benefits and possibilities of data mining in digital library, including: speed improvement; information service improvement; decision -making support; personal information service support; information processing automation, and other activities to improve the performance and utility of digital library.